2017
DOI: 10.1002/ajhb.23003
|View full text |Cite
|
Sign up to set email alerts
|

2D:4D digit ratio is associated with cognitive decline but not frailty in community‐dwelling older adults

Abstract: We cannot ascertain any contribution of prenatal exposure to androgens to the frailty status of community-dwelling elderly people. We found that reduced prenatal exposure to testosterone in women may contribute to the prevention of cognitive decline in elderly women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
2
1
Order By: Relevance
“…Moreover, there was no significant relationship between 2D:4D and the performance of patients with AD or tauopathy in different memory tasks. Our results do not agree with previous studies on this topic in which the authors describe both higher [ 48 ] and lower [ 49 , 50 ] 2D:4D in female AD patients, higher 2D:4D in male AD patients compared with controls [ 49 ] and several associations with memory task performance [ 43 , 44 ]. Compared to these investigations, our study differs primarily in terms of sample characterization and diagnostic procedures.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Moreover, there was no significant relationship between 2D:4D and the performance of patients with AD or tauopathy in different memory tasks. Our results do not agree with previous studies on this topic in which the authors describe both higher [ 48 ] and lower [ 49 , 50 ] 2D:4D in female AD patients, higher 2D:4D in male AD patients compared with controls [ 49 ] and several associations with memory task performance [ 43 , 44 ]. Compared to these investigations, our study differs primarily in terms of sample characterization and diagnostic procedures.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, most other studies in the field describe significant findings for females. Goncalves et al (2017) [ 44 ] found a significant positive correlation with the Mini-Mental State Examination (MMSE) score [ 45 ] in women, suggesting a preventive effect of low androgen exposure in utero for females. In a magnetic resonance imaging (MRI) study of healthy women, the volume of the left posterior hippocampus, a brain region often atrophic in AD [ 46 ], was lower in females with masculinized 2D:4D [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research regarding adult sex hormones and age-related cognitive decline and dementia has yielded mixed results [96]. One study regarding 2D:4D ratios found a statistically significant correlation between 2D:4D ratio and Mini-Mental State Examination scores in women, suggesting that lower prenatal exposure to testosterone is associated with lower cognitive decline [115]. Potential mechanisms behind associations of 2D:4D ratios with cognitive decline and dementia are currently not well understood.…”
Section: Prenatal Sex Hormone Exposurementioning
confidence: 99%